Naskah Rencong Handschrift (93 E 1 PNRI) Analisis Struktur dan Aspek Islam - Muhammad Haidar Izzuddin (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2022)
Manuscript 93 E 1 is a manuscript in the Rencong/Ulu script which is stored in the Archipelago Manuscript Collection Service, the National Library of the Republic of Indonesia. This manuscript is known to contain incantations/mantras and has a part that is related to Islamic aspects. This manuscript consists of three parts, namely jampi tepung, duwa kasi ala, and prayer in Arabic. This study aims to explain the general description of the 93 E 1 text, describe the structure of the 93 E 1 text, and explain the elements of Islamic teachings contained in the 93 E 1 text. This study uses a qualitative descriptive method and uses the theory of the structure of the mantra and the main elements of the teachings Islam. The results of this study are Manuscript 93 E 1 has a structure consisting of a title, an opening element, an element of suggestion, and an element of purpose/closing. The element of purpose of this manuscript is only found in the part of jampi tepung, as a repellent for reinforcements for the establishment/placement of houses in tepung tawar tradition. As for the aspects of Islam in the text only reaches the level of faith regarding faith in Allah (ilahiyat), the Messenger (nubuwat), and the last days (sam'iyyat). Keywords: jampi, Ulu script, structure, Islamic aspects